The use of complementary and alternative medicine by adults with allergies: a Czech national representative survey - Jitka Pokladnikova; A-La Park; Jan Draessler; Anna Lukacisinova; Irena Krcmova (BMC, 2021)
Abstract Background The prevalence rates of the use of Complementary and Alternative Medicine (CAM) in allergy patients range from 42% in the United States up to 50% in Europe. In the Czech Republic, no such data exists. Our aim was to examine patterns in CAM use in populations with self-reported allergies in the Czech Republic. Methods A cross-sectional survey was conducted. A sample of citizens aged 15 years and older, sex, age, and region-stratified, was randomly selected from the 2014 voter registration lists (n = 8,395,132). Respondents with self-reported allergies were further analyzed. Results Overall, 93% of the respondents with self-reported allergies reported the use of 1 or more CAM modalities during the past 30 days. Herbal teas, relaxation techniques, a detoxifying diet, dietary supplements (excluding vitamins and minerals), and reflexology were used in respondents with allergies. Females, under age 30, with higher education, higher income, and self-reported poor health, were significantly associated with the use of CAM among respondents with allergies. Conclusions The prevalence of CAM use among people with self-reported allergies in the Czech Republic is higher compared to other countries, with determinants of CAM varying across specific CAM categories. More attention to existing use is needed to promote the healthy adoption of CAM by raising awareness of its safe and effective use, both for CAM users as well as for health care providers.